HUBUNGAN KEKUATAN OTOT QUADRICEPS DENGAN STABILITAS FUNGSIONAL PADA PASIEN PASCA REKONSTRUKSI ANTERIOR CRUCIATE LIGAMENT - Gede Wahyu Pratama Wijaya; I Putu Gde Surya Adhitya; Anak Agung Gede Angga Puspa Negara; Indah Pramita (IKesT Muhammadiyah Palembang, 2024)
Introduction: Assessing the importance of muscle strength and functional stability in post-ACL reconstruction (ACLR) patients demands an in-depth understanding of how physical factors correlate with knee functional stability. Therefore, this study aims to determine the relationship between quadriceps muscle strength and functional stability in ACLR patients in the Indonesian ACL Community. Methods: This research design is observational analytic with a cross-sectional approach. The research subjects were 26 ACLR patients from the Indonesian ACL Community in Bali. This study used a hand-held dynamometer to measure quadriceps muscle strength and a single hop test to measure functional stability. Results: In the results of the Spearman Rho analysis, it was found that there was a significant relationship between quadriceps muscle strength and functional stability, as evidenced by the p-value = 0.000 (p <0.05) and the correlation coefficient value of 0.644 and positive. In addition, the multivariate results showed that subjects with poor quadriceps muscle strength were consistently associated with poor functional stability scores with odds 13.5 times higher than subjects with good quadriceps muscle strength p=0.013 (p<0.05). Discussion: It can be concluded that there is a significant relationship between quadriceps muscle strength and functional stability in ACLR patients at ACL Community Indonesia.